2021
DOI: 10.1029/2020jc016475
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Iron Deposition Alters the Ecosystem and Carbon Balance of the Indian Ocean Over a Centennial Timescale

Abstract: The Indian Ocean accounts for around one-fifth of the ocean net primary production (Behrenfeld & Falkowski, 1997a) and contains two of the largest oxygen (O 2) minimum zones (OMZs) of the world oceans in the northern part (the Arabian Sea and the Bay of Bengal) (Stramma et al., 2010). In these two regions, phytoplankton growth is generally limited by macronutrients because of the relatively shallow mixed layer and the Ekman downwelling that transports nutrients away from the euphotic layer. Furthermore, the lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…However, the comparability of the annual mean pCO 2 could have a certain level of confidence associated with the annual and long-term projections. Variations in the choice of iron scheme and/or the coefficients can influence both seasonal iron supply and subsequent phytoplankton growth and ecosystem carbon (Pham & Ito, 2021). In this sensitivity study, since the same iron model was used across the runs without re-calibration of coefficients, we attribute the differences in results to other components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the comparability of the annual mean pCO 2 could have a certain level of confidence associated with the annual and long-term projections. Variations in the choice of iron scheme and/or the coefficients can influence both seasonal iron supply and subsequent phytoplankton growth and ecosystem carbon (Pham & Ito, 2021). In this sensitivity study, since the same iron model was used across the runs without re-calibration of coefficients, we attribute the differences in results to other components.…”
Section: Discussionmentioning
confidence: 99%
“…The biological and biogeochemical components of the model are based on the 6 phytoplankton version of the Darwin model (Dutkiewicz et al, 2015) with improved representation of iron biogeochemistry including three classes of iron-binding ligands, sedimentary and hydrothermal iron sources, and interactions between particulate and dissolved iron (Pham & Ito, 2021). Furthermore, this model represents the iron limitation on the photosynthetic efficiency and the variable iron to carbon ratio in the biological parameterizations.…”
Section: Model Configurations and Experimental Designmentioning
confidence: 99%
“…Trace elements in water-soluble leach (termed as X S ; X is the specific TE) are one of the key factors responsible for the modulation of primary productivity in surface water of the ocean. ,, The average concentrations of soluble TE (Fe, Mn, and Cu) measured in this study are tabulated in Table and shown in Figure . A relatively higher Fe S concentration is seen in NCOT (27.1 ± 7.2 and 4.8 ± 2.2 ng m –3 ) followed by SCOT (17.6 ± 16.2 and 0.8 ± 0.7 ng m –3 ) and COT (7.5 ± 5.9 and 1.5 ± 1.4 ng m –3 ), with the lowest average found in OOT (2.9 ± 1.4 and 0.6 ± 0.5 ng m –3 ), during SSD-40 and SSD-55, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Key gaps associated with the FL bacteria physiology include, for instance, their Fe acquisition strategies and the role of Fe in their metabolism, as well as the interactions between FL bacteria, phytoplankton, and zooplankton. In addition, we did not consider in our model the bacterial production of specific ligands, like siderophores (Amin et al, 2009;Boiteau et al, 2016;Bundy et al, 2018), which could strengthen the interactions between Fe, bacteria, and phytoplankton (Guieu et al, 2019;Ito et al, 2016;Krishnamurthy et al, 2009;Pham & Ito, 2021). More broadly, our model, as for other ocean biogeochemistry models representing bacteria (Stock et al, 2020), only considered carbon-oxidizing free-living bacteria.…”
Section: Broader Implicationsmentioning
confidence: 99%